“Extraordinary Female Affection”: The Ladies of Llangollen and the Endurance of Queer Community - Brideoake, Fiona (Romanticism on the Net)

(untitled) (Université de Montréal, 2004)
AbstractThis essay explores romantic responses to Lady Eleanor Butler and Miss Sarah Ponsonby, known as the Ladies of Llangollen, arguing that Anna Seward and Anne Lister celebrated the Ladies’ relationship in order to melancholically enact the same-sex ties they were themselves unable to maintain. Hailed as both pioneering lesbians and chaste romantic friends, Butler and Ponsonby may appear unlikely candidates for queer recuperation. Their place within romantic literary history is equally contentious, their status as a female couple challenging notions of singular and masculine romantic subjectivity, and their creative production diverging from canonical textual forms. This essay nonetheless claims Butler and Ponsonby as queer romantics, arguing that the indeterminacy of their bond constitutes a commensurately queer resistance to definition. Their romanticism is similarly disclosed by that of their romantic acolytes, who lauded the Ladies’ home as an ideal of lasting affective community. Drawing on Judith Butler’s account of gender melancholia, this essay claims that Seward and Lister identified Butler and Ponsonby as embodying the hopes of queer community foreclosed in their own lives. Accordingly, they protected and promulgated the Ladies’ relationship in order to melancholically enact the same-sex attachments they were unable to establish enduringly or mourn publicly. In celebrating a model of flourishing female desire, Seward and Lister thus melancholically preserved their own lost love-objects, and affirmed the future instantiation of enduring queer communities.